1995
DOI: 10.1044/jshr.3802.273
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Prediction of Severity in Commonly Occurring Voice Problems

Abstract: The relative effectiveness of three acoustic measures (jitter, shimmer, and harmonic/noise ratio) in predicting the dysphonic severity of a diverse clinical population singly and together was investigated. Phonatory samples were recorded from 20 normal subjects and 60 patients representing 3 laryngeal groups (nodules, paralysis, and functional). The phonatory samples were evaluated by 22 listeners using a 7-point equal-appearing interval scale. Shimmer produced a bivariate correlation of 0.54 with dysphonic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 18 publications
5
42
1
5
Order By: Relevance
“…Note that four correlations reached significance at the highest p≤.001 level. Correlations between perturbation and harmonics to noise measures have been observed previously ( Wolfe et al, 1995;Yumoto et al, 1984). Table 3 shows the correlations between the six perceptual parameters and the four acoustic measures.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Note that four correlations reached significance at the highest p≤.001 level. Correlations between perturbation and harmonics to noise measures have been observed previously ( Wolfe et al, 1995;Yumoto et al, 1984). Table 3 shows the correlations between the six perceptual parameters and the four acoustic measures.…”
Section: Resultssupporting
confidence: 68%
“…In the present study, PPQ showed high correlations with both APQ and NNEa. The relationship between jitter and harmonics-tonoise ratio has previously been observed by Yumoto and colleagues (1984) and by Wolfe et al (1995). Yumoto et al suggested that jitter contributes to the magnitude of the noise components in the harmonics-to-noise-ratio (HNR).…”
Section: Fig 5 Rank Ordered Ascending Mean Values For the Four Acoumentioning
confidence: 67%
“…There was also a nonsignificant difference in improvement between G1 and G2 (table 23). The etiologic subgroups, however, showed irregular tendencies in improvement (tables [24][25][26][27]. The hyperfunctional group showed significant/highly significant improvement in SQ, CQ and SI in the post-test results, while the phonasthenia group showed highly significant improvement in peak flow, minimum flow, and OQ.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this shows that CPP and L/H ratio in sustained vowels are useful measurements to objectively assess the voices of esophageal speakers. Previous studies have stated that CPP is a useful measurement for distinguishing larynx-related voice trouble from normal voice and has a high correlation with the seriousness of voice disorder, as well as auditorily scaled features such as breathiness and roughness, supporting the effectiveness of cepstral analysis in cases in which audio examination fails [15,16,17,26,27]. Moreover, the L/H ratio showed a high correlation with breathiness and with higher sensitivity and specificity as reported previously [17], indicating its usefulness in detecting voice problems.…”
Section: Discussionmentioning
confidence: 98%
“…Here, as jitter, shimmer and NHR are F0-based variables, all seemed to have a high correlation with CPP, which is a variable reflecting harmonic organization and therefore F0. The high correlation between mean CPP F0 and F0 implies that, in basic frequency analysis, cepstral measurements representing the degree of harmonic organization could be as useful as the spectral measurement F0 [15,26,27]. …”
Section: Discussionmentioning
confidence: 99%